DEVELOPMENT AND VALIDATION ANALYSIS OF ACYCLOVIR TABLET CONTENT DETERMINATION METHOD USING FTIR - Nugrahani, Ilma; Mussadah, Mega Vianita (International Journal of Applied Pharmaceutics, 2016)
Objective: The aim of this research is to develop the fourier transforms infrared spectroscopy (FTIR) as an alternative method for determination acyclovir content in the tablet dosage form. Methods: Infra-red spectrum of acyclovir were transformed to be its first derivative, then measured the AUC (area under the curve). Calibration curve was made in a series of the concentration of 0.2-1.2% w/w, and some wavenumbers spectra's area were choiced. Some validation parameters: specificity, linearity, limit of detection, limit of quantification, accuracy and precision were evaluated, then this validated method was used to determine the content of acyclovir in three tablet dosage forms found from the market. Results: The optimal wavenumber obtained was shown at 3700-3440 cm-1, next it was used during validation test, which produced the excellent yields of all validation parameters. Furthermore, this method was used for tablets content determination. Conclusion: All the results from this research showed that FTIR can be used as a validated alternative method, more rapid and simple for determine the content of acyclovir in a tablet.